Discordance of 3rd and 4th generation QuantiFERON-TB Gold assays by pregnancy stages in India - Vandana Kulkarni; Mallika Alexander; Ramesh Bhosale; Divyashri Jain; Prasad Deshpande; Emily Shira Gitlin; Arthi Vaidyanathan; Andrea Chalem; Shilpa Naik; Nikhil Gupte; Neelu Nawani; Amita Gupta; et al. (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Pregnancy and HIV affect CD4+ T lymphocytes and impact performance of QuantiFERON-TB Gold (QFT). We compared the results of QFT with QuantiFERON-TB Gold Plus (QFT-Plus), which also measures CD8+ responses to TB antigens, during pregnancy and postpartum. Methods: We screened 516 pregnant women for TB infection (TBI) with IGRA. From 165 IGRA + pregnant women, QFT vs QFT-Plus results were compared at delivery and postpartum. Longitudinal changes in QFT-Plus were assessed in 74 pregnant women who received QFT-Plus testing at pregnancy, delivery, and postpartum. Results: Through cross-sectional analysis of the IGRA + cohort, QFT-Plus showed higher positivity than QFT (80 % vs 65 %, p = 0.04) at delivery but no difference postpartum. Among 35 women with HIV, QFT-Plus returned more positive results than QFT at delivery and postpartum (76 % vs 47 %, p = 0.08; 90 % vs 80 %, p = 0.54), though not statistically significant. Longitudinally, QFT-Plus positivity by TB1 or TB2 was highest antepartum vs. delivery and postpartum (74 % vs. 58 % vs. 62 %; p = 0.09) and performed better than TB1 alone (100 % vs 90 %, p = 0.04) in women without HIV but not in women with HIV. Conclusions: Performance of QFT-Plus was consistent across pregnancy, including at delivery when QFT positivity is lower. QFT-Plus may enhance antenatal TBI detection among pregnant women.